Hubungan Antara Jenis Makanan, Frekuensi Makan Dan Hygiene Gigi Dengan Kejadian Karies Gigi Pada Siswa - Boekoesoe, Lintje; Amalia, Lia; Lareko, Julianeristawati I; Ahmad, Zul Fikar (Madu : Jurnal Kesehatan, 2023)
Dental caries or cavities are among the most common dental and oral diseases, especially in children, because children prefer sweet foods or drinks that can cause dental caries. The study aimed to determine the relationship between the type of food, frequency of eating, and dental hygiene with the incidence of dental caries in students. This type of research is observational analytic with a cross-sectional approach. The population was all students at SDN 09 Paleleh; the sample was 113 students at SDN 09 Paleleh with a total sampling technique—data analysis using Chi-square statistical test. Type of food consumed obtained p-value 0.000 (α ≤ 0.05), frequency of eating food consumed obtained p-value 0.001 (α ≤ 0.05), hygiene habits brushing teeth obtained p-value 0.009 (α ≤ 0.05), hygiene frequency brushing teeth obtained p-value 0.086 (α ≥ 0.05). There is a relationship between the type of food consumed, the frequency of eating food consumed, and the hygiene of tooth brushing habits with the incidence of dental caries in students. There is no relationship between the hygiene of the frequency of brushing teeth and the incidence of dental caries in students. Suggestions for students: It is expected to reduce the consumption of cariogenic foods and increase the frequency and habits in brushing teeth so that teeth and mouth are healthier to avoid caries.